Outcomes of endovascular treatment for acute large‐vessel ischaemic stroke more than 6 h after symptom onset. (25th September 2017) - Motyer, R.; Kok, H. K.; Asadi, H.; O'Hare, A.; Brennan, P.; Power, S.; Looby, S.; Nicholson, P.; Williams, D.; Murphy, S.; Hill, M. D.; Goyal, M.; et al.
Abstract: Background and Objectives: Benefit from endovascular thrombectomy (EVT) for large‐vessel occlusion (LVO) acute ischaemic stroke (AIS) is well demonstrated. Furthermore, emerging evidence supports efficacy in appropriately selected patients treated beyond current recommendations of 6 h. We evaluated clinical outcomes in patients undergoing late EVT at our institution. Methods: Retrospective review of prospectively collected clinical database on 355 patients who underwent EVT for LVO AIS. Data collected consisted of patient demographics, radiological findings and outcome details. Outcomes, including 90‐day functional status, recanalization, symptomatic intracranial haemorrhage (sICH) and 90‐day mortality, for patients undergoing EVT <6 h, >6 h, and >7.3 h, were compared. Results: A total of 355 patients underwent EVT for LVO AIS at our institution during the review period, with 74 (21%) patients treated ≥6 h from symptom onset. Successful recanalization was achieved in 285 (80%) patients, with 228 (81%) achieving a mTICI ≥2b in the <6 h group, and 57 (77%) in the >6 h group ( P = 0.429). Ninety‐day functional independence (mRS 0–2) was achieved in 162 (46%) patients, with 130 (46%) achieving a mRS of 0–2 in the <6 h group, and 32 (43%) in the >6 h group ( P = 0.643). No significant differences were found in rates of sICH or 90‐day mortality. No significant differences in functional independence, recanalization rates, sICH or mortality were identified in patients treated with EVT >7.3 h compared to <7.3 h. Conclusions: In appropriately selected patients, EVT >6 h was associated with comparable outcomes to those treated <6 h. These data support a physiological approach to patient selection.